Interface engineering of hierarchical NiCoP/NiCoSx heterostructure arrays for efficient alkaline hydrogen evolution at large current density. Issue 41 (13th October 2022) - Han, Weiwei; Zhang, Fan; Qiu, Lingshu; Qian, Yang; Hao, Shaoyun; Li, Ping; He, Yi; Zhang, Xingwang
Abstract : Hierarchical NiCoP/NiCoS x heterostructure grown on Ni foam (NiCoP/NiCoS x /NF) exhibits outstanding electrocatalytic activity and stability for alkaline hydrogen evolution reaction under large current density. Abstract : The development of non-noble metal electrocatalysts with high activity and long-term stability for the hydrogen evolution reaction (HER), especially at large current density, is of great significance for industrial hydrogen production from water using renewable electricity. Constructing heterostructures with interfacial interactions is an effective strategy to improve the catalytic performance for large-current-density HER. Herein, we innovatively present a facile two-step electrodeposition method to immobilize a hierarchical NiCoP/NiCoS x heterostructure on Ni foam (NF) for alkaline HER. The strong interfacial coupling effect between NiCoP and NiCoS x not only offers abundant active sites for fast electrochemical reaction, but also enhances the charge transfer ability accompanied by high electrical conductivity. Consequently, the obtained self-supporting NiCoP/NiCoS x /NF exhibits an excellent catalytic performance with low overpotentials of 68, 144 and 222 mV to deliver current densities of 10, 100 and 500 mA cm −2 in 1 M KOH, along with good stability for more than 110 h, outperforming most of the reported non-noble metal based HER catalysts. Density functional theory (DFT) results further confirm that this bimetal phosphide/sulfide heterostructure can synergistically optimize the Gibbs free energy of H* during the HER process, thus accelerating the HER reaction kinetics. This work provides a new strategy toward the rational design of large-current-density electrocatalysts, which have great potential in practical large-scale hydrogen production.